2003
DOI: 10.1034/j.1600-0447.2003.00167.x
|View full text |Cite
|
Sign up to set email alerts
|

No association between two polymorphisms at the5HT2Agene and bipolar affective puerperal psychosis

Abstract: The results indicate that variation at two common polymorphisms of the 5HT2A gene does not appear to play a major role in the development of bipolar affective puerperal psychosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 31 publications
(37 reference statements)
1
4
0
1
Order By: Relevance
“…Elevated frequencies of the A allele were also reported to be associated with susceptibility to anorexia nervosa (Collier et al, 1997) and criminal behavior by Swedish males (Berggard et al, 2003). Although no associations between 5-HT2A receptor gene polymorphisms and anorexia nervosa (Ziegler et al, 1999) or bipolar affective disorder (Robertson, Jones, Middle, Moray, & Craddock, 2003) have been reported, behavioral studies in healthy adult humans support the idea of a significant association between them in the continuous performance task and the Go/No-Go task. discovered that a gene polymorphism in the 5-HT2A receptor (A-1438G) modulates impulsive behavior (responses for non-target stimuli) in a Go/No-Go task and indicated that incentive feedback in the results of the participants' responses signifies individual differences.…”
Section: -Ht 2a Gene Polymorphismsupporting
confidence: 47%
“…Elevated frequencies of the A allele were also reported to be associated with susceptibility to anorexia nervosa (Collier et al, 1997) and criminal behavior by Swedish males (Berggard et al, 2003). Although no associations between 5-HT2A receptor gene polymorphisms and anorexia nervosa (Ziegler et al, 1999) or bipolar affective disorder (Robertson, Jones, Middle, Moray, & Craddock, 2003) have been reported, behavioral studies in healthy adult humans support the idea of a significant association between them in the continuous performance task and the Go/No-Go task. discovered that a gene polymorphism in the 5-HT2A receptor (A-1438G) modulates impulsive behavior (responses for non-target stimuli) in a Go/No-Go task and indicated that incentive feedback in the results of the participants' responses signifies individual differences.…”
Section: -Ht 2a Gene Polymorphismsupporting
confidence: 47%
“…We have previously reported 1) compelling evidence that a vulnerability to postpartum bipolar episodes clusters in families (8) and 2) data suggesting that a vulnerability to puerperal episodes is a marker for a more familial form of bipolar disorder (10). Additionally, we have reported a number of candidate gene association studies in women with puerperal psychosis (27) and have shown suggestive, although preliminary, evidence for an association between puerperal psychosis and a variant at the serotonin transporter gene on chromosome 17 (28). In the present study, we employed the complementary, positional approach of a genomewide linkage study in sibling pairs, focusing on those families in which a female proband has suffered an episode of mania or psychosis within 6 weeks of delivery.…”
Section: Discussionmentioning
confidence: 95%
“…Evidence from a linkage study indicated the possible location of a susceptibility gene on chromosome 16 . Particular candidate genes, such as those involved in the serotoninergic hormonal and inflammatory pathways, have also been investigated. It is hoped that identifying the genetic factors that increase risk will lead to more individualised risk assessment, earlier identification of women at risk, and improved treatments for women who become ill.…”
Section: Aetiology and Pathophysiologymentioning
confidence: 99%